MeBo70 Seabed Drilling on a Polar Continental Shelf: Operational Report and Lessons From Drilling in the Amundsen Sea Embayment of West Antarctica. (17th November 2017) - Gohl, K.; Freudenthal, T.; Hillenbrand, C.‐D.; Klages, J.; Larter, R.; Bickert, T.; Bohaty, S.; Ehrmann, W.; Esper, O.; Frederichs, T.; Gebhardt, C.; Küssner, K.; et al.
Abstract: A multibarrel seabed drill rig was used for the first time to drill unconsolidated sediments and consolidated sedimentary rocks from an Antarctic shelf with core recoveries between 7% and 76%. We deployed the MARUM‐MeBo70 drill device at nine drill sites in the Amundsen Sea Embayment. Three sites were located on the inner shelf of Pine Island Bay from which soft sediments, presumably deposited at high sedimentation rates in isolated small basins, were recovered from drill depths of up to 36 m below seafloor. Six sites were located on the middle shelf of the eastern and western embayment. Drilling at five of these sites recovered consolidated sediments and sedimentary rocks from dipping strata spanning ages from Cretaceous to Miocene. This report describes the initial coring results, the challenges posed by drifting icebergs and sea ice, and technical issues related to deployment of the MeBo70. We also present recommendations for similar future drilling campaigns on polar continental shelves. Key Points: First operation of a multibarrel seabed drill device in Antarctica Eleven holes at nine sites with max drilled depth of 35.7 m and recovery of 7%–76% Cores sampled Cretaceous to Holocene shelf sediments